2020
DOI: 10.1017/ice.2020.278
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nine surface disinfectants against Candida auris using a quantitative disk carrier method: EPA SOP-MB-35

Abstract: We tested 9 disinfectants against Candida auris using the quantitative disk carrier method EPA-MB-35-00: 5 products with hydrogen peroxide or alcohol-based chemistries were effective and 4 quaternary ammonium compound-based products were not. This work supported a FIFRA Section 18 emergency exemption granted by the US Environmental Protection Agency to expand disinfectant guidance for C. auris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 6 publications
4
38
0
Order By: Relevance
“…C. auris isolates from the 2 clades were studied because a recent report suggested that a clade IV isolate of C. auris (AR 0385) was less susceptible to low concentrations of sodium hypochlorite than a clade II isolate (AR 0381). 8 Testing was completed in triplicate. Log 10 colony-forming unit (CFU) reductions were calculated by comparing recovery from treated versus untreated control carriers.…”
Section: Methodsmentioning
confidence: 99%
“…C. auris isolates from the 2 clades were studied because a recent report suggested that a clade IV isolate of C. auris (AR 0385) was less susceptible to low concentrations of sodium hypochlorite than a clade II isolate (AR 0381). 8 Testing was completed in triplicate. Log 10 colony-forming unit (CFU) reductions were calculated by comparing recovery from treated versus untreated control carriers.…”
Section: Methodsmentioning
confidence: 99%
“…auris colonisation in this study was the axillary temperature monitoring with contaminated reusable digital thermometers. These findings may be related to the use of quaternary ammonium disinfection, 22 and most patients hospitalised during the outbreak were admitted due to severe COVID‐19 and had a similar clinical course.…”
Section: Discussionmentioning
confidence: 93%
“…auris ‐colonised patients that were isolated and put in contact precautions. These measures, along with the substitution of disinfection products based on quaternary ammonium by sodium hypochlorite and hydrogen peroxide‐based disinfectants, 22 and replacement of all digital thermometers by infrared ones were instituted. Despite all these measures, the outbreak was not controlled, and additional screening cultures are under evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The United States Center for Disease Control and Prevention (CDC) identifies C. auris as a major global threat, with fatality rates in immunocompromised individuals ranging from 10-60% [1] . Finding safe and effective non-toxic disinfectants against C. auris has proven difficult [2] , [3] , [4] , [5] , [6] . The plant oil Isomerized Linoleic acid has maintained Generally Recognized as Safe (GRAS) status as a food additive since 2008 [7] .…”
Section: Introductionmentioning
confidence: 99%